Contact force and ablation assessment of surgical bipolar radiofrequency clamps in the treatment of atrial fibrillation. (29th June 2018) - Varzaly, Jason A; Chapman, Darius; Lau, Dennis H; Edwards, Suzanne; Louise, Jennie; Edwards, James; Mahajan, Rajiv; Worthington, Michael; Sanders, Prashanthan
Abstract: OBJECTIVES: Atrial fibrillation is treated surgically by creating conduction block lesions. Radiofrequency (RF) lesions have reduced efficacy compared to 'cut-and-sew'. Catheter ablation studies demonstrate a relationship between lesion depth and contact force. We hypothesized that contact force and lesion depth are dependent on design of the bipolar surgical RF clamps. METHODS: Hinged and parallel jaw style RF clamps were studied. Muscle samples were clamped with pressure-sensitive film at increasing tissue thicknesses. Films were analysed determining clamp pressure profiles. A sheep model was utilized for ablation testing using each clamp style until the device indicated transmurality. Separate muscle areas had 1, 2 or 3 burns applied. The muscle was excised, sectioned every 1 cm and stained for lesion depth and fat thickness analysis. RESULTS: Pressure profiling comparing the proximal and distal segments of each clamp style demonstrated only one statistically significant difference in the parallel clamp; the hinged clamp had statistically significant differences ( P ≤ 0.03) for all tissue thicknesses. There was no evidence for differences in the proximal lesion depth of both clamps ( P = 0.13) but deeper distally in the parallel clamp (10.17 mm vs 8.02 mm, P = 0.003). The logistic regression analysis demonstrated increased odds of transmurality with parallel clamps at 1, 2 or 3 burns ( P = 0.03, P = 0.003 and P = 0.002). Every 1 mm increase in overlying fat decreased likelihood of transmurality by 11% ( P < 0.05). CONCLUSIONS: The parallel and hinged clamps have different pressure profiles with higher likelihood of transmurality using the parallel clamp. Fat reduces the ability of RF to deliver a transmural lesion. These findings have implications for optimal surgical RF ablation technique.